Comparative study of the transcatheter and transthoracic device closure treatments for atrial septal defect: A Chinese single-institution experience. Issue 11 (March 2017) - Chen, Qiang; Cao, Hua; Chen, Zhao-yang; Zhang, Gui-Can; Chen, Liang-wan; Xu, Fan; He, Jia-jun
Abstract : Abstract: The purpose of this study was to compare patient populations, safety, feasibility, complications, and total costs of the transcatheter and transthoracic device closure treatments for secundum atrial septal defect. From January 2014 to December 2014, we enrolled 155 patients with secundum atrial septal defects in our hospital. The patients were divided into 2 groups: the 70 patients in group A underwent transcatheter device closure, and the 85 patients in group B underwent transthoracic intraoperative device closure with a right lateral mini-thoracotomy. In group A, the total occlusion rate was 94.3% immediately after the operation, 100% at 3 months, and 100% at 12 months of follow-up; the group A results were not statistically different from the group B results (94.1%, 98.8%, 98.8%, respectively). There was a statistically significant difference in the minor complication rate ( P < 0.05), and there were no reported deaths. There was a greater indicated scope using the transthoracic closure device to treat atrial septal defects. In our comparative study, the patients in group B had longer intensive care unit stays and hospital stays than group A ( P < 0.05). Both of the device closure treatment options for secundum atrial septal defect are safe and feasible. The transcatheter device closure approach has the advantages of more cosmetic results, less trauma, and a shorter hospital stay than the transthoracic approach. On the contrary, the transthoracic closure device is an economical alternative choice, particularly for patients who are not eligible for the transcatheter closure device.